Quality of Life and Related Factors in Discharged Patients with COVID-19 - Jinzhuo HU; Wenhuan WU; Jinwen SUN; Wei ZHANG; Shu CHENG; Zicheng GAO; Jinghua QIAN (康复学报)
Objective:To determine the factors associated with quality of life of discharged patients with coronavirus disease 2019(COVID-19), so as to provide a basis for optimizing early intervention programs, preventing community from life restriction, and formulating appropriate community rehabilitation measures.Methods:A total of 57 discharged patients with COVID-19 who were cured from Wuhan China resources& Wisco general hospital from March to April 2020. In the"Questionnaire Star"platform from April to May 2020, the 12-item short form health survey version 2(SF-12V2) was used to evaluate life quality of life; the self-rating anxiety scale (SAS) was used to evaluate dyspnea anxiety status; the self-rating depression scale (SDS) was used to evaluate depression status; the modified medical research council dyspnea scores (mMRC) was used to evaluate difficulty of breathing. The quality of life of discharged patients with COVID-19 with different characteristics was compared. The correlation between the quality of life of patients and anxiety, depression and dyspnea and the related factors were analyzed.Results:A total of 57 questionnaires were distributed, and three duplicate and invalid questionnaires were eliminated, 54 valid questionnaires were obtained, with an effective questionnaire of 94.74%.①Quality of life of discharged patients with COVID-19: the physical component summary (PCS) scores and mental component summary (MCS) scores were (37.02±12.32) and (38.46±14.42) respectively; there were 3 cases (5.56%), 45 cases (83.33%), 5 cases (9.26%), and 1 case (1.85%) with dyspnea grade 0 to 3 respectively; 19 cases (35.19%) had an anxiety state (SAS≥50), and 19 cases (35.19%) had an anxiety state (SDS≥53). ②Comparison of quality of life of COVID-19 patients with different characteristics: patients with different disease types showed statistically significant differences in the SF-12V2 PCS(P< 0.05). ③Correlation analysis between quality of life, anxiety, depression and dyspnea: Pearson's correlation indicated that, anxiety (r=-0.34, P=0.011) and dyspnea (r=-0.39, P=0.003) were negatively correlated with the PCS scores, anxiety (r=-0.46, P=0.001) and depression (r=-0.40, P=0.002) were negatively correlated with the MCS scores.④Analysis of influencing factors on the quality of life of COVID-19 patients: multiple linear regression indicated that, sex (β=8.27), depression (β=-0.34) and severity of illness (β=-11.68) were significant predictors of the SF-12V2 PCS scores (P< 0.05). Anxiety (β=-0.62) was a significant predictor of the SF-12V2 MCS scores (P< 0.05).Conclusion:COVID-19 patients discharged from the hospital have problems with dyspnea, anxiety, depression, and the decline of quality of life. Sex, depression, anxiety and severity of illness are important factors for the decline of quality of life in patients with COVID-19. Patients with COVID-19(especially female patients and severe patients) should be screened for depression and anxiety as soon as possible after discharge and intervention should be carried out to reduce patients'negative emotions. Patients should be encouraged to participate in rehabilitation training appropriately to improve respiratory function and improve the quality of life.